PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SD NEGERI 78 PEKANBARU - Dahlia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
Mathematics teaching that is done in class VB SDN 78 Pekanbaru not get satisfactory results from the results of the evaluation are still many students who get the value under the KKM (70). From 36 grade VB, only reaching the KKM is as much as 11 students (30,55%), and who have not yet reached KKM as much as 25 students (69,44%) with the value of the average results of learning mathematics is 56,67. The aim of the research to improve the results of learning mathematics grade VB SDN 78 Pekanbaru with the implementation of cooperative learning model STAD types on the matter arose space. By using this method STAD has increased significantly student learning outcomes. Improving student learning results VB class at cycle I the first meeting of 11.86 from the value of the average cycle with enough pre category. Then on the second meeting of the cycle I return increased by 6.64 with enough category. After held reflection, then held the improvement at cycle II. At the first meeting of increasing the value of the average from the previous cycle of 2.25 with enough category, then held after improvement in the reflection of the second meeting of the average value increased by 3.61 with good category. Based on the analysis of the data and the discussion in obtain the conclusion that the implementation of cooperative learning model STAD types used as actions that are done in SDN 78 Pekanbaru has been able to improve the results of learning mathematics students in the classroom VB especially on the subject of learning the operation count mixed with whole numbers. It is expected that the teachers at SDN 78 Pekanbaru in order to implement cooperative learning model STAD types on the lessons of mathematics as one of the alternative learning that can improve the results of student learning.